SECONDARY HYPERTHYROIDISM PRESENTING WITH MASSIVE STROKE - Krishnan, K.J.Lingeswary; Mohamad, Masni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperthyroidism secondary to pituitary adenoma is rare (TSHoma). It comprises 1-3% of all pituitary adenomas. TSHoma itself does not directly cause strokes; however, the associated hyperthyroidism predisposes patients to cardiovascular complications, including atrial fibrillation and hypertension, thereby increasing the risk of stroke. CASE A 54-year-old Malay female complained of sudden-onset right-sided body weakness, aphasia, and confusion. Clinical examination revealed rapid atrial fibrillation (AF) and neurological deficits consistent with a left middle cerebral artery (MCA) territory infarct. CT scan of the brain showed a sellar mass. Initial investigation revealed elevated FT4 levels, with nonsuppressed TSH, prompting further diagnostic workup to confirm secondary hyperthyroidism. Her remaining pituitary functions were normal. Transthoracic echocardiography showed normal ventricular size, mild MR, AR, and moderate TR; however, there was no left ventricular thrombus. Pituitary MRI later showed a 1.9 x 1.9 x 3.2 cm pituitary macroadenoma with suprasellar extension. AF was subsequently controlled with a beta blocker and direct oral anticoagulants (DOACs) were initiated. Hyperthyroidism was managed with octreotide LAR and biochemical euthyroidism was achieved, and the patient showed neurological improvement. CONCLUSION TSHoma-associated with stroke is rarely reported. Hyperthyroidism-induced cardiovascular complications are well-documented, including the risk of stroke. Treatment strategies for TSHoma aim to control hyperthyroidism and alleviate associated complications. While surgical resection is the definitive treatment, medical therapy with somatostatin analogues may be considered, as demonstrated in this case. The management of TSHoma is challenging due to its association with hyperthyroidism-induced cardiovascular complications, and the risk of stroke. Recognizing TSHoma and early intervention may prevent its cardiovascular complications.